Bank leverage and stock liquidity: evidence from BRICS countries. Issue 3 (1st August 2016) - Umar, Muhammad; Sun, Gang
Abstract : Purpose: The purpose of the study is to explore the relationship between bank leverage and stock liquidity. Design/methodology/approach: A simultaneous equations model and a two-stage least squares method were used to find the above-mentioned relationship, using data from all the listed banks of the BRICS countries, for the years 2007-2014. Findings: A decrease in leverage results in lower stock liquidity of the banks. Bank leverage is a significant determinant of stock liquidity, but changes in stock liquidity do not explain the variation in bank leverage. However, in the case of small banks, an increase in stock liquidity results in lower leverage. In the case of large banks, bank leverage and stock liquidity are significant determinants of each other, and the relationship between them is positive. Practical implications: An increase in high quality capital, as required by the Basel III accord, will result in lower stock liquidity of the banks in emerging markets. However, stock liquidity shocks do not affect the leverage of banks. Originality/value: To the best of the authors'knowledge, this study is the first one to explore the relationship between leverage and stock liquidity of financial firms. It contributes to the existing literature on bank liquidity and capital structure and helps managers and policy makers to formulate better policies.